Divorce Lawsuit on the Reason Husband is Addicted to Online Gambling - Desvia, Lusiana; An, Rusydi; Yandi, Akmal; Febria, Thomas; Huzaemah, Umu (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Suiting for divorce on the grounds that the husband is addicted to online gambling is an increasingly disturbing phenomenon in today's modern society. This article aims to dig deeper into the impact of online gambling addiction on marital relationships and the resulting divorce process. The data collection method in this research was carried out through literature study which includes scientific articles, journals and other trusted sources. In this research, we will analyze how online gambling addiction can affect the dynamics of husband and wife relationships, the factors that trigger online gambling addiction in husbands, as well as the psychological and social impact it has in the divorce process. It is hoped that the results of this research will provide deeper insight into this problem and contribute to efforts to prevent and overcome online gambling addiction in marital relationships.